HUBUNGAN NEGARA DAN AGAMA DALAM NEGARA PANCASILA - budiyono, budiyono (FIAT JUSTISIA, 2014)
Relations among the state and religion in the state of Pancasila, wherein the first principle of Pancasila is Belief in the one and only God asserted that Indonesia is not a country which is based on a religion and not a state that separates religion and state. But countries that believe in the existence of God, wherein the state puts the religion and belief as spirit of integrity of the Unitary Republic of Indonesia. Relations among the state and religion are interdependent relations, where in religion gives spirituality in the nation and state, while the state guarantees religious life.Â Keywords: State, Religion, Interdependent.